Answer:
12
Step-by-step explanation:
Answer:
X=-2
Y=-6
Step-by-step explanation:
Since both equations are already expressed in the simplest form of y, then we equate them to be equal hence
x-4=4x+2
Bringing like terms together
-4-2=4x-x
Solving both sides
-6=3x
Making x the subject then
X=-6/3=-2
Subsrituting the value of x into any of the initial equations
Y=x-4 then y=-2-4=-6
Therefore, the solution is
X=-2
Y=-6
Answer:
Wait
Step-by-step explanation:
I solve first
1/2 of angle D is given as 32 degrees.
The 3 inside angles need to add up to 180 degrees.
Angle B is a right angle, which is 90.
Angle C = 180 - 90 - 32 = 58 degrees.
The graph represents y=-4x-1
If you notice the line, it goes past the -1 on the y axis which indicates that the y intercept is -1 since that was the only choice which displayed this, we know that our answer is y=-4x-1